Pentingnya Administrasi Sarana dan Prasarana Pendidikan - Annisaa Nur Faudillah; Armanila Armanila; Aulia Fitriani Munthe; Rizka Khairi (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Educational infrastructure makes a significant contribution to achieving the goals of education. The better the facilities and infrastructure, the more successful the teaching and learning process in education will be. Management of educational facilities and infrastructure is very important to support the achievement of learning planning facilities and infrastructure in achieving educational goals. The teaching and learning process will be more successful if educational facilities and infrastructure are sufficient. For this reason, educational institutions and infrastructure are very important. It is hoped that facilities and infrastructure can be utilized appropriately according to PBM's needs. This research uses: Qualitative methods using literature reviews. The results of this research will help the management of educational facilities and infrastructure in a comprehensive process that is planned and implemented well, and can develop sustainable education objects by being always ready to be used in the learning process, so that the learning process contributes more effectively and efficiently to achieving the educational goals that have been set. achieved, and can be used as a requirement in the use or maintenance of educational facilities and infrastructure implemented by the school. Keywords : Facilities, infrastructure, education